The Role of Very Low Level Blast Overpressure in Symptomatology - Sajja, Venkata Siva Sai Sujith; LaValle, Christina; Salib, Jonathan E.; Misistia, Anthony C.; Ghebremedhin, Meron Y.; Ramos, Alejandro N.; Egnoto, Michael Joseph; Long, Joseph B.; Kamimori, Gary H. (Frontiers in Neurology, 2019)
Blast overpressure exposure has been linked to transient, but measurably deteriorated performance and symptomatologies in law enforcement/military personnel. Overlapping sub-concussive symptomatology associated with the very low level blast overpressures (vLLB) but high sound pressure (<3psi) associated with these exposures has largely been ignored. Notably, the current vLLB or acoustic literature has focused exclusively on auditory defects, and has not addressed the broader concerns of Soldier health and readiness. This work was prompted by reports of symptomatology such as headache, nausea, slowed reaction time, and balance/hearing complications among personnel undergoing frequent exposures to low overpressure accompanied by high acoustic pressures. To more fully address the consequences associated with low overpressure exposures (<3psi), a pilot proof-of-concept study was implemented, and data was acquired at two sites on the Fort Benning grenade course range. Findings indicated overpressures ranged from 0.14-0.42 psi (0.97 – 2.89 kPa) at range 1 and 0.22 – 0.30 psi (1.52 – 2.07 kPa) on range 2 of the grenade course. Corresponding sound-meter data varied from 153.72 - 163.22 dBP. Headache and long think were the most frequently reported symptoms (3/6 instructors), with lightheadedness, ringing of the ears, restlessness, frustration, and irritability also increasing in 2/6 of the instructors post exposure. Long think (prolonged thinking), ringing of the ears, restlessness, and irritability were the most severe symptoms, with the highest reported post exposure value rating a 3 on the 0-4-point scale. We demonstrate that low-level repeated overpressure exposure can result in transient symptomatology that overlaps with sub-concussive like effects.